An Introduction to Technological Support for Writing - Greer, Nick; Teevan, Jaime; Iqbal, Shamsi (Microsoft Research, 2016)
This paper provides a brief introduction to opportunities that exist for providing better technological support for writing. Developing the appropriate technology that adequately supports the complex processes of writing is difficult because writing requires fundamental but varied skills such as reading, analysis, reasoning, and communication. For this reason, we believe that writing tools can provide a valuable lens by which to understand and explore interesting problems related to information work. While a number of tools have been developed to support the processes of writing involving composition, editing, organization and formatting, little exists to support the underlying cognitive processes of writing that help shape up the core content, and we believe that this represents a worthwhile opportunity for study. Here we give an overview of why writing is important and what is currently known about the writing process, and then discuss how this leads to new ways to thinking about building tools to support the writing process.